Evolución del concepto de sociedad unipersonal (2013)
The present paper provides an analysis of the figure of the one- person society two stages. At first, we study how this figure has been understood by the doctrine and comparative law. In the second stage, we review the evolution and current status of the member company in Colombia and a critical analysis of the legislation and jurisprudence on the matter.